Secondary Subtalar Joint Osteoarthritis Following Total Ankle Replacement. (October 2019) - Sokolowski, Marc; Krähenbühl, Nicola; Wang, Chen; Zwicky, Lukas; Schweizer, Christine; Horn Lang, Tamara; Hintermann, Beat
Background: An advantage of total ankle replacement (TAR) compared to ankle fusion is that by maintaining motion, the occurrence of hypermobility of adjacent joints may be prevented. This could affect the development of symptomatic subtalar joint osteoarthritis (OA). The aim of the study was to determine the incidence of subtalar joint fusion and the progression of subtalar joint OA following TAR. Methods: Secondary subtalar joint fusion rate was determined from a cohort of 941 patients receiving primary TAR between 2000 and 2016. The indication for fusion, the time interval from primary TAR to fusion, and the union rate were evaluated. To assess the progression of subtalar joint OA, degenerative changes of the subtalar joint were classified in 671 patients using the Kellgren-Lawrence score (KLS) prior to TAR and at latest follow-up. Results: In 4% (37) of the patients, a secondary subtalar joint fusion was necessary. The indication for fusion was symptomatic OA in 51% (19), hindfoot instability in 27% (10), osteonecrosis of the talus in 19% (7), and cystic changes of the talus in 3% (1) of the patients. Time from primary TAR to subtalar joint fusion due to progressive OA was 5.0 (range, 0.3-10) years and for other reasons 1.6 (range, 0.2-11.6) years ( P = .3). In 68% (456) of the patients, no progression of subtalar joint OA was observed. Conclusion: The incidence of secondary subtalar joint fusion was low. The most common reason for subtalar joint fusion following TAR was symptomatic OA. Level of Evidence: Level IV, case series.